Effect of risk factors on the outcomes of COVID-19-infected intensive care patients: a single-center retrospective study - Sapra, Aditya; VU, Jagadeeswaran; Jha, Shyamal; HN, Madhusudana; Muzammil, Mohammad; Majumdar, Meghna; Arya, Jeet Singh; Sheoran, Aarti (Journal of Ideas in Health, 2022)
Background: To date, little attention has been paid to the impact of risk factors on the outcome of patients with coronavirus disease 2019 (COVID-19) hospitalized in the intensive care unit (ICU). This study was performed to examine the effects of risk factors on death among COVID-19 patients hospitalized in the ICU. Methods: From April 2020 to November 2020, data on 141 COVID-19-infected intensive care patients at 7 Air Force Hospital, Kanpur, were retrospectively retrieved. All analyses were performed using SPSS statistical software (SPSS Inc., Chicago, IL, USA, 15.0). Bivariate and multivariate logistic regression analysis was done to identify independent risk factors. A p-value <0.05 was considered statistically significant. Results: Most of study population were males (69.5%) with mean age of 59.8 ± 17.5 years. Out of 141 patients, 60 (42.6%) patients had comorbidities and 81 (57.4%) patients had no comorbidities. ICU death rates were 46.1%. Bivariate logistic regression analysis revealed that male sex (OR:0.45;95%CI:0.21-0.94), diabetes mellitus (OR:2.96; 95%CI:1.16-7.54), coronary artery disease (OR:2.48;95%CI:0.83-7.37), chronic kidney disease (OR:0.13,95% CI:0.02-1.12), patients with one (OR:1.25,95%CI:0.54-2.86) or more than two comorbidities (OR:1.95,95%CI:0.81-4.70), and who required high flow oxygen therapy (OR:13.30,95%CI:5.81-30.43), non-invasive (OR: 0.10,95% CI:0.02-0.45) and invasive ventilators (OR:0.04,95%CI:0.02-0.09) all were associated with higher ICU death rates. Multivariable logistic regression found following independent risk factors for death: patients with one comorbidity (OR:0.10;95%CI:0.02-0.66), non-invasive ventilator (OR:0.005;95%CI:0.000-0.091), and invasive ventilator (OR:0.003;95%CI:0.000-0.032). Conclusion: Identification of risk factors is of utmost importance to reduce death in COVID-19 infected intensive care patients.